Plan S in Latin America: a precautionary note - Debat, Humberto Julio (2020)
Background: Latin America has historically led a vital and open access movement andleads the worldwide region with the adoption of wider open access practices. Argentina has expressed its commitment to join Plan S, an initiative from a European consortiumof research funders with a mandate to promote the open access publishing of scientific outputs. Analysis: This opinion article suggests that the potential adhesion of Argentina orother Latin American nations to Plan S ignores the reality and tradition of Latin American open access publishing. Conclusion and implications: Plan S must demonstrate that it will encourage at aregional and global level the advancement of non-commercial open access initiatives.Latin America should invest and promote open nonprofit scholarly-led infrastructures, allowing the academy to regain control of scholarly communications.